YOUNG GENERATION PROBLEMATICS OF POST-EDUCATION IN THE NOVEL "ANGKATAN BARU" BY HAMKA - Abdillah, Abdillah; Pratiwi, Dita Ayu R (Jurnal Sabilarrasyad, 2020)
The purpose of writing this journal is to explain the behavior patterns of young generations of high education that are problematic in society. The young generation is highly educated in the Novel "Angkatan Baru" by Hamka to tell the young generation of higher education but is unacquainted with the hard work and reluctantly devoting themselves to high paying. Science only becomes jewellery for him, not used for benefits and for many people. Younger generations are good at reading books, but are not good at reading people. The writing in this journal uses qualitative Enelitian using a descriptive method. Because it described the depiction of the young generation or youth in the Novel of the Buya Hamka "Angkatan Baru". This method was chosen to assess the growing problems in life especially for young generations after attending higher education in college. The data source used is the Novel "Angkatan Baru" by Hamka.